Developing an informal mentoring relationship in career advancement and psychosocial of young graduate entrepreneurs for human resource development. - Zainal Abiddin, Norhasni (Medwell Publishing, 2013)
Mentoring is a professional relationship or partnership between a mentor who shares his professional experience with a mentee for the purpose of empowering the mentee with similar business issues. This study examines the roles of informal mentors on the young graduates who are the novices in managing commercial agricultural projects. This is a qualitative study where respondents are involved in in-depth interviews to explore information and to answer the research questions. The respondents are five young graduates who are now successful entrepreneurs in their own ventures of commercial agriculture. The data of the interviews was analyzed manually to answer the research questions. This study has indentified the primary functions of an informal mentor on career success and psychosocial for Human Resource Development (HRD). HRD is a process of developing and/or unleashing human expertise through organization development and personnel training and development for the purpose of improving performance at the organization, process and individual levels. It can be concluded that informal mentoring has its significant influence on the entrepreneurs, particularly on the young graduates. The major implication of this study are using informal mentoring support of a selective basis can make a positive different to new firm formation, survival and growth and the educating role of informal mentoring support can be exploited to help young entrepreneurs to develop their own networks. Suggestions for improvements in start-up mentoring program are discussed.